Report on: Interaction with farmers and extensionists for understanding technological gap for the Sustainable Intensification of wheat in Morocco - Devkota, Krishna; Devkota Wasti, Mina Kumari (International Center for Agricultural Research in the Dry Areas, 2023)
Wheat is the major crop in Rabat-Sale-Kenitra region, contributing to more than 25% of the national wheat production. Despite its significance, the region has challenges such as low productivity, risk of crop failure, low input use efficiency, over or under-application of input, etc. Addressing these issues requires comprehensive training, demonstration, capacity building, and awareness programs. The adoption of ‘Good Agricultural Practices’ has been found promising for sustainable intensification. To this end, ICARDA and Institut National de la Recherche Agronomique (INRA) are conducting a series of on-station experiments focused on achieving sustainable intensification of wheat-based systems.